Legal Responsibility for Environmental Damage Due to Failure to Implement Corporate Social Responsibility: Pertanggungjawaban Hukum Atas Kerusakan Lingkungan Akibat Tidak Terlaksananya Corporate Social Rensponsibility - Perkasa, Dwiki Putra; Lubis, Putri Mei Lestari (Academia Open, 2026)
General Background: Environmental degradation caused by business activities indicates suboptimal Corporate Social Responsibility (CSR) implementation within the legal framework. Specific Background: CSR has been regulated under Law Number 40 of 2007; however, its application remains limited, particularly for companies in the natural resources sector, and lacks explicit criminal sanctions. Knowledge Gap: There is a normative vacuum and regulatory inconsistency between CSR obligations and environmental law enforcement, which weakens legal certainty and accountability. Aims: This study analyzes CSR regulation and examines legal sanctions applicable to corporate actors responsible for environmental damage based on normative legal analysis of statutory provisions and legal doctrines. Results: The findings reveal that CSR obligations are sectorally restricted and inadequately supported by sanction mechanisms in corporate law, although environmental violations can still be addressed through administrative, civil, and criminal sanctions under Law Number 32 of 2009. Weak enforcement practices further limit deterrence. Novelty: The study integrates CSR within environmental law discourse by emphasizing the legal consequences of non-implementation and identifying structural regulatory gaps. Implications: Strengthening regulatory coherence, expanding CSR obligations across sectors, and ensuring consistent enforcement are essential to position CSR as a legally binding instrument supporting sustainable development and corporate accountability. Highlights• Regulatory inconsistency creates legal uncertainty in corporate obligations• Sanction mechanisms rely primarily on environmental law instruments• Enforcement limitations reduce deterrence against environmental violations KeywordsCorporate Social Responsibility; Environmental Law; Legal Responsibility; Regulatory Gap; Sustainable Development